High-Resolution Rb Two-Photon Transition Spectroscopy by a Femtosecond Frequency Comb via Pulses Control - 张一驰 范鹏瑞 元晋鹏 汪丽蓉 肖连团 贾锁堂 (Chinese physics letters, 2016)
We experimentally observe the high resolution direct frequency comb spectroscopy using counter-propagating broadband femtosecond pulses on two-photon transitions in room-temperature ^87 Rb atoms. The Doppler broad- ened background is effectively eliminated with the pulse shaping method and the spectrum modulation technique. The combination of the pulse shaping method and the spectra modulation technique provides a potential approachto reduce background of at least 99%.